Professional development for sessional staff in higher education: a review of current evidence. Issue 2 (23rd February 2018) - Hitch, Danielle; Mahoney, Paige; Macfarlane, Susie
ABSTRACT: The aim of this study was to provide an integrated review of evidence published in the past decade around professional development for sessional staff in higher education. Using the Integrating Theory, Evidence and Action method, the review analysed recent evidence using the three principles of the Benchmarking Leadership and Advancement of Standards for Sessional Teaching project – Quality Learning and Teaching, Sessional Staff Support and Sustainability. Quality Learning and Teaching refers to issues affecting the quality of sessional staff teaching and learning, while Sessional Staff Support refers to the provision of consistent support and inclusive infrastructure for sessional staff. The Sustainability principle refers to practices that encourage the retention of good sessional staff and the pursuit of quality teaching. Clear themes emerge from the evidence that suggest long-standing structural issues that are yet to be effectively addressed. However, several examples of effective strategies were also identified, particularly around peer observation and mentorship.